KONTEN EDUKATIF TIKTOK: ANALISIS USES AND GRATIFICATION PADA PENYUSUNAN SKRIPSI - Putri Sang Begawan, Pramudya Kansa; Ranteallo, Ikma Citra; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 4 No 1 (2024): JISSOROT, 2024)
The TikTok application is an audio visual application that is currently being widely used by teenagers, including students. TikTok application offers various conveniences in social media, TikTok is able to provide media for anyone who wants to spread knowledge or entertainment. The movement of the TikTok algorithm which follows the interests of its users is able to make it easy for users to get the information they need easily. Currently, TikTok is also able to provide benefits for students, with the presence of creators with high educational backgrounds so that these creators are able to provide the knowledge they have to the general audience of TikTok users. A person's need to obtain information can also be fulfilled by the TikTok application, starting from educational content, entertainment content, and also about news, both national and international, all on TikTok. The focus of this research is to find out whether there is a relationship between the use of the TikTok application as an educational medium in students' thesis work in reviewing the uses and gratifications theory. This research uses a mix method research method, where this research will be analyzed using quantitative methods and qualitative methods simultaneously. The samples and informants in this research were students from Udayana University who were working on their thesis and actively using the TikTok application, and some were academic figures and also content creators on TikTok.